Use of Information Resources and Library Services by Students of the University of Horticultural Sciences, Karnataka State, India - Parvathamma, N.; Shinde, Mukesh M. (Journal of Information and Knowledge, 2015)
The University of Horticultural Sciences was established in Karnataka State with headquarter in Bagalkote on 22 November 2008 by the Government of Karnataka, India. A survey of the use of information resources and library services by the students of eight Colleges of Horticulture, affiliated to the University of Horticultural Sciences was undertaken. Students enrolled for undergraduate course constitute 84.14% of the total student population. Hence, the findings of the study are biased towards the undergraduate students. Findings of the study reveal that majority of the students visit library daily or at least twice in a week and spend less than two hours during their visit. They visit library to borrow text books, general books in Horticulture and allied fields, read newspapers, magazines, and Indian and foreign journals. Reference sources such as dictionaries, encyclopedia are consulted rarely. Majority of the students never accessed bibliographic databases on CD/ROM or DVD and web resources. This may be due to the ignorance about the academic value of these resources or lack of technical skills. The situation calls for training them in information literacy skills to identify, locate, evaluate and use both print and electronic information resources efficiently, so that they can become independent and life long learners. Further, Reference service and Book lending service are very frequently used by the students. Photocopying facility is occasionally used or never used by majority of the students. It is necessary to provide Photocopying facility at affordable cost, which also helps in minimizing the misuse of print resources in the library.